Flamingos - Gish, Melissa (Mankato, MN : Creative Education, 2014)
"A scientific look at flamingos, including their habitats, physical characteristics such as their coloration, behaviors, relationships with humans, and numbers of the tropical birds in the world today"--
Includes bibliographical references and index.
Keywords: Flamingos -- Juvenile literature